Implementasi Plasma Tegangan Tinggi Untuk Pengolahan Limbah Cair Industri Minyak Sawit - nadeak, Parade; Murdiya, Fri; Andrio, David (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Water pollution due to waste has become a concern of environmental activists recently. Many technologies have become alternatives to overcome this, such as the use of high voltage plasma.High-voltage plasma technology is included in green technology because it does not use chemicals and with high-voltage plasma technology, processing waste is faster, does not require large areasof land and is environmentally friendly. This research aims to reduce Biochemical Oxygen Demand (BOD) compounds, chemical Oxygen demand (COD), total suspended solid (TSS) by utilizing highvoltage plasma. The method used is to generate plasma using a Neon Power Supply transformer with the voltage of 8 kV and with a frequency of 21 kHz. The plasma is generated by using rod andplate electrodes. Based on the results of plasma experiment, it is able to reduce BOD, COD, TSS compounds in palm waste. In this study the test was carried out with different distances of 2 mmand 4 mm with a time of 20 minutes, 30 minutes, 40 minutes and 60 minutes. This test shows that a distance of 2mm is faster to reduce BOD, COD TSS than a distance of 4mm.Keywords: Plasma, high voltage, liquid waste, BOD, COD, TSS